Inhibition of AKR1B10-mediated metabolism of daunorubicin as a novel off-target effect for the Bcr-Abl tyrosine kinase inhibitor dasatinib - Büküm, Neslihan; Novotná, Eva; Morell, Anselm; Želazková, Jana; Laštovičková, Lenka; Čermáková, Lucie; Portillo, Ramon; Solich, Petr; Wsól, Vladimír (Biochemical pharmacology, 2021)
Bcr-Abl tyrosine kinase inhibitors significantly improved Philadelphia chromosome-positive leukaemia therapy. Apart from Bcr-Abl kinase, imatinib, dasatinib, nilotinib, bosutinib and ponatinib are known to have additional off-target effects that might contribute to their antitumoural activities. In our study, we identified aldo-keto reductase 1B10 (AKR1B10) as a novel target for dasatinib. The enzyme AKR1B10 is upregulated in several cancers and influences the metabolism of chemotherapy drugs, including anthracyclines. AKR1B10 reduces anthracyclines to alcohol metabolites that show less antineoplastic properties and tend to accumulate in cardiac tissue. In our experiments, clinically achievable concentrations of dasatinib selectively inhibited AKR1B10 both in experiments with recombinant enzyme (Ki = 0.6 µM) and in a cellular model (IC50 = 0.5 µM). Subsequently, the ability of dasatinib to attenuate AKR1B10-mediated daunorubicin (Daun) resistance was determined in AKR1B10-overexpressing cells. We have demonstrated that dasatinib can synergize with Daun in human cancer cells and enhance its therapeutic effectiveness. Taken together, our results provide new information on how dasatinib may act beyond targeting Bcr-Abl kinase, which may help to design new chemotherapy regimens, including those with anthracyclines.
Keywords: buňky A549; Molecular Docking Simulation; aldo-keto reduktasy; simulace molekulového dockingu; sekundární struktura proteinů; HCT116 Cells; Humans; Antineoplastic Agents; chemorezistence; bcr-abl fúzní proteiny; Aldo-Keto Reductases; protinádorové látky; Dasatinib; Protein Kinase Inhibitors; daunomycin; inhibitory proteinkinas; HCT116 buňky; Drug Delivery Systems; Drug Resistance, Neoplasm; Protein Structure, Secondary; Fusion Proteins, bcr-abl; Dose-Response Relationship, Drug; lékové transportní systémy; vztah mezi dávkou a účinkem léčiva; Daunorubicin; lidé; dasatinib; A549 Cells